Frog-derived peptides and neuroprotection - Moreira, Daniel C.; Batagin-Neto, Augusto [UNESP]; Leite, José Roberto S.A. (Elsevier, 2024)
The incidence of age-related diseases (e.g., neurodegenerative diseases) is increasing as the world’s population lives longer. Neurodegeneration, the dysfunction and loss of neurons, is a hallmark of chronic (e.g., Alzheimer’s disease and Parkinson’s disease) and acute (e.g., stroke) pathological conditions for which current treatment is less than ideal. This has motivated the search for novel therapeutic agents, including peptide drugs. In the last years, peptides found in the skin secretion of amphibians have shown neuroprotective activity under experimental conditions. This chapter provides an overview of the studies that have investigated the neuroprotective potential of peptides isolated from the skin secretion of anurans. Six peptides, including two ocellatins and two tryptophyllins, originally found in the skin secretion of five anuran species are covered. The evidence for the neuroprotective activity of these peptides mainly stems from their ability to modulate microglia activation and the redox metabolism, key therapeutic targets for treatment of neurodegeneration. Other targets, such as mitogen-activated protein kinase-related signaling components, have also been investigated. Despite the necessity of further studies to elucidate the underlying mechanisms of action, as well as their pharmacokinetics and pharmacodynamics, peptides from the skin secretion of anurans hold promise as therapeutic agents for neurodegenerative diseases.
Keywords: Antioxidant; hypoxia; ischemia; microglia; neurodegeneration; oxidative stress